Hierarchy of Groups Evaluation Using Different F-Score Variants - Spytkowski, Michał; Olech, Łukasz P.; Kwaśnicka, Halina (Intelligent Information and Database Systems, 2016)
The paper presents a cursory examination of clustering, focusing on a rarely explored field of hierarchy of clusters. Based on this, a short discussion of clustering quality measures is presented and the F-score measure is examined more deeply. As there are no attempts to assess the quality for hierarchies of clusters, three variants of the F-Score based index are presented: classic, hierarchical and partial order. The partial order index is the authors’ approach to the subject. Conducted experiments show the properties of the considered measures. In conclusions, the strong and weak sides of each variant are presented.